System of information processing of corroding plane stress structure deformation - Науменко, Наталья Юрьевна; Ляшенко, Оксана Анатольевна (Eastern-European Journal of Enterprise Technologies, 2012)
A new approach to building a mathematical model of corroding structures and the generalized structure information processing system of the object under study, taking into account the peculiarities of its operation. Proposed phased construction of a mathematical model